Mathematical modeling and control of wind energy electric conversion system feeding standalone load - Rayaguru, N K; Poornachandra Rao, N.; Navin Sam, K.; Kumar Thakur, Sunil (International Journal of Engineering and Technology, 2017)
In this paper, state space model of the complete Wind Energy Electric Conversion System (WEECS) comprising of wind turbine, Permanent Magnet Synchronous Generator (PMSG), uncontrolled rectifier, DC-DC boost converter, and SPWM inverter feeding a standalone load has been formulated. The derived state space model is then simulated using Matlab/Simulink to test the model. As the standalone three phase load connected to the inverter demands constant output voltage irrespective of intermittent wind pattern, a PI controller is used to control the duty ratio of DC-DC boost converter to maintain constant output voltage at the inverter end.